2013
DOI: 10.1186/1742-4755-10-19
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal care packages with reduced visits and perinatal mortality: a secondary analysis of the WHO Antenatal Care Trial

Abstract: BackgroundIn 2001, the WHO Antenatal Care Trial (WHOACT) concluded that an antenatal care package of evidence-based screening, therapeutic interventions and education across four antenatal visits for low-risk women was not inferior to standard antenatal care and may reduce cost. However, an updated Cochrane review in 2010 identified an increased risk of perinatal mortality of borderline statistical significance in three cluster-randomized trials (including the WHOACT) in developing countries. We conducted a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
99
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 11 publications
7
99
0
3
Order By: Relevance
“…7,28,29 Other studies show that mean gestational age at start of ANC was lower, (<16 weeks gestation). 30,31 But the mean age at start of ANC shown by other studies was higher, (>20 weeks gestation). 28,29 Difference in study setting, time when the studies were carried out, and study design are some of the reasons that account for the difference in the results we obtained and that seen in other studies.…”
Section: Discussionmentioning
confidence: 82%
“…7,28,29 Other studies show that mean gestational age at start of ANC was lower, (<16 weeks gestation). 30,31 But the mean age at start of ANC shown by other studies was higher, (>20 weeks gestation). 28,29 Difference in study setting, time when the studies were carried out, and study design are some of the reasons that account for the difference in the results we obtained and that seen in other studies.…”
Section: Discussionmentioning
confidence: 82%
“…Concerns [9,[31][32][33] have been raised by women and service providers about fewer visits and spacing of visits. Secondary analysis of the WHO 2001 randomized control trial of focused antenatal care showed excess of foetal deaths in those who had fewer visits [34]. Studies have suggested that the long interval between visits from 32-36 weeks could result in non-detection of intrauterine growth restriction and other problems that could arise and cause foetal death in the third trimester [31,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary analysis of the WHO 2001 randomized control trial of focused antenatal care showed excess of foetal deaths in those who had fewer visits [34]. Studies have suggested that the long interval between visits from 32-36 weeks could result in non-detection of intrauterine growth restriction and other problems that could arise and cause foetal death in the third trimester [31,34,35]. In implementing focused antenatal care, health care workers must be trained to spend quality time screening, treating and addressing problems that could result in adverse maternal and fetal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Numerically, more pregnant women without risk factors have seen to end up with serious adverse outcome compared to those with risk factors during the attendance of antenatal care service [3]. In order to prevent pregnancy adverse outcome world wide as well as in developing countries, interventions should therefore be targeted at all pregnant women attending antenatal care service and during childbirth [4].…”
Section: Introductionmentioning
confidence: 99%